Availability and Use of Woody Plant Resources in Two Areas of Caatinga in Northeastern Brazil - Trindade, Madson Reis de Oliveira; Jardim, Jomar Gomes; Casas, Alejandro; Guerra, Natan Medeiros; Lucena, Reinaldo Farias Paiva de (Ethnobotany Research and Applications, 2015)
Traditional knowledge of woody plants from the vegetation type known as caatinga was documented in the rural communities of João Câmara, Rio Grande do Norte, and Remígio, Paraíba, in northeastern Brazil. The relationship between the species availability and their local importance or use value (the “ecological apparency hypothesis”) was evaluated based on the calculation of three types of use value: UVgeneral, UVactual, and UVpotential. A phytosociological study was conducted using the point-centered quarter method for sampling 4000 individual plants in the two communities studied. Semi-structured ethnobotanical interviews about the use and human cultural role of plants were carried out with 92 local participants (49 women and 43 men). The correlation between ethnobotanical and phytosociological data was analyzed using the Spearman correlation coefficient. A total of 58 useful plant species, belonging to 42 genera of 18 plant families, was recorded in interviews. Through the phytosociological study, 30 species belonging to 22 genera and 12 families in João Câmara, and 34 species of 22 genera from nine families in Remígio, were recorded. The ecological apparency hypothesis was supported in João Câmara, which showed positive correlations between UVgeneral and dominance (rs = 0.49; p <0.02) and UVactual and dominance (rs = 0.43; p <0.04), but not in Remígio. Analyzing the data per use categories showed that only the technology category exhibited a positive correlation between UVpotential and dominance (rs = 0.60; and p <0.03). Ecological apparency could explain better the relationship between the local availability and the use value of the timber resources. The point-centered quarter method was efficient to test the ecological apparency hypothesis.